THE EXISTENCE OF EQUALITY EDUCATION SYSTEM IN PESANTREN SALAFIYAH - Asrizal Saiin (Universitas Islam Malang, 2021)
The study in this manuscript discusses the impact on the educational equalization system of Pesantren Salafiyah and designs how Pesantren Salafiyah has always existed in the world of modern education. This research belongs to the type of qualitative study using the document analysis method. The form of data analysis used is descriptive analysis. The research approach method in this paper is library research. This study is divided into four methods, namely, the method of determining the subject, the form of the study, the method of data collection, and the method of data analysis. The result is the ability of Pesantren Salafiyah to make certain accommodations and concessions to find a pattern that they consider appropriate enough to face modernization and changes that are increasingly fast and have a broad impact without sacrificing the essence and other basic things in the existence of the pesantren, so that Pesantren Salafiyah still exists in the midst of the hustle and bustle of modernizing Islamic education